Anti-malarial artesunate ameliorates atherosclerosis by modulating arterial inflammatory responses via inhibiting the NF-κB–NLRP3 inflammasome pathway - Cen, Yanyan; Xiong, Yalan; Qin, Rongxin; Tao, Hui; Yang, Qunfang; Pan, Xichun (Frontiers in Pharmacology, 2023)
Introduction: Chronic inflammation plays a critical role in the pathogenesis of atherosclerosis (AS), and involves a complex interplay between blood components, macrophages, and arterial wall. Therefore, it is valuable in the development of targeted therapies to treat AS. Methods: AS rat model was induced by atherogenic diet plus with lipopolysaccharide (LPS) and then treated by anti-malarial artesunate (Art), a succinate derivative of artemisinin. The arterial morphology was observed after Oil red O, hematoxylin—eosin, and Masson’s staining. The arterial protein level was detected by immunohistochemistry or immunofluorescence. The expression level of mRNA was determined by PCR array or real-time PCR. Results: Herein, we showed that Art possessed a dose-dependently protective effect on AS rats. In detail, Art showed a comparable inhibitory effect on arterial plaque and serum lipids compared to those of rosuvastatin (RS), and further showed a better inhibition on arterial lipid deposition and arterial remodeling comprised of arterial wall thicken and vascular collagen deposition, than those of RS. The improvement of Art on AS rats was related to inhibit arterial macrophage recruitment, and inhibit nuclear factor κB (NF-κB)-related excessive arterial inflammatory responses. Critically, Art showed significant inhibition on the NLRP3 inflammasome activation in both arterial wall and arterial macrophages, by down-regulating the expression of NOD-like receptor thermal protein domain associated protein 3 (NLRP3) and apoptosis associated speckle-like protein containing CARD (ASC), leading to less production of the NLRP3 inflammasome—derived caspase-1, interleukin-1β (IL-1β), IL-18, and subsequent transforming growth factor β1 (TGF-β1) in AS rats. Conclusion: We propose that Art is an anti-AS agent acts through modulating the arterial inflammatory responses via inhibiting the NF-κB – NLRP3 inflammasome pathway.